2021
DOI: 10.3390/cryst11121442
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation-Induced Crystal Nucleation and Morphology of Dried Poly(Vinylidene Fluoride) Droplets

Abstract: The evaporation of a polymer solution droplet is important in solution-based polymer film fabrications, such as inkjet printing, spray coatings, and droplet casting, etc. In this work, we investigated the effect of droplet size, solvent evaporation rate, and concentration on the “coffee-ring” effect, crystal nucleation, polymorphism, and morphology of dried poly(vinylidene fluoride) (PVDF) solution droplets with the atomic force microscopy (AFM) and two-dimensional grazing incidence wide angle X-ray scattering… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…What's more, as shown in Fig. 7(c-2), the γ phase is shown as a mountain like crystal in the phase image [37], which means that there are a large number of γ phase in PCNT-61, which is consistent with previous discussion in Fig. 6.…”
Section: Aggregation Structure Of Pn Pgn and Pcntsupporting
confidence: 87%
“…What's more, as shown in Fig. 7(c-2), the γ phase is shown as a mountain like crystal in the phase image [37], which means that there are a large number of γ phase in PCNT-61, which is consistent with previous discussion in Fig. 6.…”
Section: Aggregation Structure Of Pn Pgn and Pcntsupporting
confidence: 87%
“…The circular symmetry in spherulites results in the well-known Maltese cross and centrosymmetric birefringence under a cross-polarized optical microscope. Great efforts have been made to elucidate the relationship between the lamellar orientation and the spherulitic birefringence in polymer melts, blends, and solution-casting films. Those fundamental studies are the basis to understand the optoelectronic or electrooptical properties in semiconductors, solar cells, and light-emitting devices. Recent progress in droplet-processing techniques, i.e., inkjet printing, , 3D printing, , ultrasonic spray, and microfluidics, , further requires precise control of polymer crystals and optical properties on micro- or nanometer scales, which is an emerging area to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…13−28 Those fundamental studies are the basis to understand the optoelectronic or electrooptical properties in semiconductors, solar cells, and light-emitting devices. 29−32 Recent progress in dropletprocessing techniques, i.e., inkjet printing, 33,34 3D printing, 35,36 ultrasonic spray, 37 and microfluidics, 38,39 further requires precise control of polymer crystals and optical properties on micro-or nanometer scales, which is an emerging area to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…At present, in addition to the review, 14 regular articles [2][3][4][5][6][7][8][9][10][11][12][13][14][15] have been published on the special topic of "polymer crystallization". These contributions span research topics ranging from molecular mechanisms of nucleation and nucleating agents to the effect of molecular structures, chain conformations and processing parameters on the nucleation and crystallization behavior of various polymers.…”
mentioning
confidence: 99%
“…Physical parameters during processing play important roles in the nucleation and crystallization of polymers. Liang and Wang [9] investigated the crystal structure and morphology of dried poly(vinylidene fluoride) solution droplets by varying the droplet size, solvent evaporation rate and concentration. It was revealed that the nucleation of βor γ-phase poly(vinylidene fluoride) at the boundary of droplets was promoted by fast solvent evaporation-induced outward capillary flow.…”
mentioning
confidence: 99%